(untitled) (Research, Society and Development, 2023)
Introduction: In the academic context, alcohol can be an escape tool for stress levels. As a result, there is a higher rate of drinking-related problems when comparing university students and individuals who do not attend college. In this work, the focus will be on medical students, since they are under high academic pressures due to the large workload and the long duration of the course. Methodology: This is an integrative review about the use of alcohol by medical students. Data from the Virtual Health Library (BVS), Scientific Electronic Library Online (SciELO) and National Library of Medicine (PubMed) bases were used, from the intersection of the descriptors “alcohol”, “alcoholism in college”, “alcohol abuse” and “medical students”, to answer the question formulated through the PICO strategy. Results and Discussion: The use of alcohol causes several damages to the consumer’s body. Thus, it is important to analyze the use/abuse of this substance by medical students, who are under great pressure due to the changes brought about by entering the university. In view of this, the causes that lead young people to alcohol abuse are highlighted, such as risky sexual behavior, accidents, smoking, use of other drugs and reduced academic performance. Conclusion: In view of the causes and losses presented in this review, it is necessary to develop studies that demonstrate the use/abuse of alcohol by medical students so that solutions can be created and adopted in colleges.